The impact of Brexit on further education mobility in northern Ireland - Salvador, Teresa Margarida Dias (2024)
As part of my Master’s Degree in Intercultural Studies for Business at the Porto Accounting and Business School (ISCAP) I completed an internship as a Project Coordinator in Belfast with Intern Europe. This internship report reflects on my experience and explores the profound impact of Brexit on student mobility within Northern Ireland's Further Education (FE) sector. By examining the region's complex historical and political context, alongside the withdrawal from the Erasmus+ programme, this study highlights the unique challenges arising from the UK's exit from the European Union and the opportunities created by the region's unique political status. Through a combination of historical analysis, policy review, and practical case studies, the findings reveal a marked decline in student and staff mobility, exacerbated by new visa regulations and the bureaucratic constraints of the Turing Scheme. Accessing comprehensive data on the effects of Brexit has proven challenging, even when engaging with government bodies, underscoring the significant gap in available information. Key insights are drawn from the case studies of Northern Regional College and North West Regional College, illustrating the significant funding reductions and operational challenges faced by these institutions. Additionally, the experience of Intern Europe, which facilitates in-bound vocational work placements under Erasmus+, emphasizes the broader organizational impacts of Brexit. The research highlights a growing distrust among EU member states regarding mobility to the UK and emphasizes the need for new policies and initiatives to restore mobility opportunities. Ultimately, this report calls for a collaborative approach to rebuilding international partnerships, enhancing funding structures, and simplifying bureaucratic processes to ensure that Northern Ireland's educational institutions can continue to provide meaningful mobility experiences in a post-Brexit world.